Pengaruh Perempuan Terhadap Pengambilan Keputusan Laki-laki dalam Novel Al Faris Al Jamil Karya Ali Ahmad Baktsir - Akmaliyah, Akmaliyah; Syasi, M.; AB, Moch. Naqieb (IAIN Pekalongan, 2020)
This research aims to reveal how the women's influence on the men's decision making in the novel Al-Faris Al-Jamil by Ali Ahmad Baktsir and the factors taht inlfuence it. The women’s influence here is how the female figures contained in the novel Al-Faris Al-Jamil influence Mushab as the main character who is a leader in making a decision. This research uses an analysis of feminist literary criticism. Meanwhile, the method used in this research is library research. The results of this study indicate that the women’s influence on male decision making in the novel Al-Faris Al-Jamil by Ali Ahmad Baktsir is shown by Sukainah, Mush'ab’s wife and Umrah, his enemy's wife. This influence is seen in the public domain because the situations and conditions told in the novel is the war. The factors for women that can influence men's decision making in the novel Al-Faris Al-Jamil by Ali Ahmad Baktsir are intelligence and beauty.